In vitro antibacterial activity of andrographolide and hordenine against methicillin-resistant Staphylococcus aureus and Staphylococcus aureus - S. J. Vidyavarsha; Bibu John Kariyil; Varsha Unni; Jess Vergis; Sanis Juliet; Preethy John; R. Anoopraj (Journal of Veterinary and Animal Sciences, 2022)
Bacterial infections are difficult to treat, especially those infected with resistant bacteria. Due to the haphazard use of antibiotics in humans and animals, methicillin-resistant Staphylococcus aureus (MRSA) has developed resistance to practically all commercially available antibacterial drugs. Exploring natural plant compounds with antibacterial activity could be beneficial in the treatment of infections with MRSA and Staphylococcus aureus. Andrographolide, a labdane diterpenoid derived from Andrographis paniculata, and Hordenine, a phenethylamine alkaloid found in Hordeum vulgare, are reported to have antibacterial activity. In the present study, the antibacterial activity of andrographolide and hordenine was tested against MRSA and S. aureus using the Kirby- Bauer agar disc diffusion method and the modified resazurin microtiter plate assay. The results of the study revealed that both andrographolide and hordenine at various concentrations did not show any zone of inhibition against MRSA and S. aureus. Hordenine showed an MIC of 1000 μg/mL against MRSA and S. aureus, but andrographolide had no effect on both MRSA and S. aureus.